(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Aphidius ervi Haliday, Aphidius sp., Ephedrus persicae Froggatt, Lysiphlebus confusus Tremblay et Eady, L. testaceipes (Cresson), Trioxys angelicae (Haliday), two unidentified Syrphid flies and one unidentified Cecidomyid, have been found as natural antagonists of Aphis parietariae Theobald in Sicily. Such parasitoids emerged from the aphid infesting Parietaria diffusa M. et K., whose samples were collected through January and May 1997, in different sites, either in citrus groves or in the neighbouring areas. We analyzed the relative abundance of every Aphidiid species: L. testaceipes was prevailing (61.8%), followed by E. persicae (13.5%), L. confusus (11.2%), T. angelicae (3.0%), and Aphidius spp. (0.2%). Furthermore, only L. testaceipes and L. confusus were regularly found all over the period of the sampling. Cynipoidea and Chalcidoidea wasps, hyperparasitoids of the above mentioned Aphidiids, have also been obtained; their first adults emerged from the samples collected during the last decade of April, reaching 10.2% on the whole. Taking into account the role that such primary parasitoids play in citrus plantations as antagonists of the main aphid pests, and that Aphis parietariae is known as infesting only plants of Parietaria spp., which grow as ruderal botanica! species, these Urticaceae should be re-evaluated as reservoir of parasitoids to be preserved in the citrus groves and in the neighbourhood.